The publisher Humphrey Moseley and royalist literature, 1640-1660 - Whitehead, N (2014)
The principal argument of this thesis is that royalist literary publishing in the civil wars and Interregnum was a more coherent and wider movement than has been recognised. It asserts the importance of print culture to royalists, both as a vehicle for personal responses to political circumstances, and as a means to criticize and undermine the opposition. The thesis uses the publisher Humphrey Moseley as a lens through which to examine the publisher's role in the dissemination of a wide range of royalist texts. It demonstrates that publishers, as well as authors, were driven by their political and ideological opinions. The thesis begins by establishing that the royalist and Anglican convictions expressed within the texts published by Moseley corresponded with his own. This opening chapter also demonstrates the editorial control that he exerted when publishing a book. Next follow five case studies. In the second chapter I examine writings of Moseley's most prolific author, James Howell. I show that until the censorship legislation of September 1649, Howell published royalist polemical pamphlets. I argue that in response to the censorship act Howell shifted to a more subtle method of polemical writing, most notably when he embedded extracts from his polemical pamphlets in his historical allegory Dodona's Grove which Moseley published in 1650. Chapters Three to Six are genre-based case studies. These chapters analyse the ways that a variety of genres were used by royalists in support of the Stuart cause and the Anglican Church. In the final chapter I set Moseley within the context of royalist publishing more widely. I review the careers of Henry Seile and Richard Royston to demonstrate that Moseley was not the only publisher committed to the royalist cause and that his productions belonged to a broad spectrum of royalist publishing.